Strategic Process and Content as Mediators Between Organizational Context and Structure - Miller, Danny; Dröge, Cornelia; Toulouse, Jean‐Marie (Academy of Management Journal, 1988)
A series of LISREL analyses showed that aspects of the strategy-making process and the content of business strategies mediate between organizational context and structure. One dimension of context, chief-executive-officer need for achievement, influences the intended rationality of the strategy-making process, which in turn influences structural formalization and integration. Another aspect of context, environmental uncertainty, relates to strategic product innovation, which in turn influences structural centralization and formalization. Finally, strategic process and content were shown to be related in a manner that orchestrates their mediation between context and structure. We suggest that the latitude for strategic choice causes context and structure to be indirectly and somewhat loosely coupled.